2017
DOI: 10.1155/2017/3941217
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of First-Line Treatments for Chemotherapy-Naive Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Indirect Comparison

Abstract: Recently, several drugs have been introduced for the first-line treatment of chemotherapy-naive metastatic castration-resistant prostate cancer (mCRPC), but few studies have compared treatment outcomes directly. This indirect comparison among 10 clinical trials (n = 4870 patients) retrieved from PubMed, Web of Science, Cochrane Collaboration, and ClinicalTrails.gov was performed to assess the safety and efficacy of docetaxel, cabazitaxel, abiraterone, enzalutamide, and sipuleucel-T for the initial treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In addition, we comprehensively explore the safety of abiraterone and enzalutamide by showing that AR inhibitors could lead to higher rates of any-grade AE occurrence, virtually significantly lower rates of high-grade (grade >=3) AE, and similar rates of AE leading to death or discontinuation. In Zheng's study 11 , they also evaluated the safety of abiraterone and enzalutamide, although less AEs were involved. Also, given that only COU-AA-302 trial and PREVAIL trial were respectively included for analysis in their study, the statistical power was relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we comprehensively explore the safety of abiraterone and enzalutamide by showing that AR inhibitors could lead to higher rates of any-grade AE occurrence, virtually significantly lower rates of high-grade (grade >=3) AE, and similar rates of AE leading to death or discontinuation. In Zheng's study 11 , they also evaluated the safety of abiraterone and enzalutamide, although less AEs were involved. Also, given that only COU-AA-302 trial and PREVAIL trial were respectively included for analysis in their study, the statistical power was relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…However, few meta-analyses have included all the related RCTs and directly pooled the HR of OS and PFS by these two agents. In addition, although some previous studies have tried to investigate the efficacy and safety of abiraterone and enzalutamide, evidence regarding AR inhibitors as a whole was scanty and their analysis was either indirect or subjected to bias caused by non-RCTs [11][12][13][14] . Moreover, comparison of the occurrence high-grade AEs (grade ≥3) between the AR inhibitor and control groups has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Study by Smit et al suggested a higher PSA response rate was associated with longer survival . Interestingly a meta‐analyses also found that ENZ had greater benefits in PFS but not in OS though number of study included in the analyses were small . A recently published systemic review has indicated ENZ group had a significantly higher PSA response rate…”
Section: Application Within “Real World”mentioning
confidence: 99%
“…Poor tolerance to previous chemotherapy generally guides the selection of a different drug class for subsequent treatment lines. 28,29 Nevertheless, as ABI and ENZ are also associated with undesirable effects, clinicians must be familiar with the diagnosis and management of these undesirable effects. 29 Recommendation 11.…”
Section: Paɵents With Mcrpcmentioning
confidence: 99%